ANALISIS KEBUTUHAN PENGEMBANGAN PERANGKAT PEMBELAJARAN TEMATIK BERBASIS PERMAINAN IMEO KAMBING UNTUK MENGEMBANGKAN PENGETAHUAN MITIGASI BENCANA GEMPA BUMI SISWA SD NEGERI KABUPATEN KEPAHIANG - Indah Rani Nur Kurnia; Dwi Anggraini; Hasnawati Hasnawati (JURIDIKDAS, 2022)
This study aims to describe the development procedure of thematic learning tools based on the imeo kambing’s game for earthquake mitigation awareness for students of Elementary Schools of Kepahiang Regency. This is a Research and Development (R&D) type of research using the ADDIE model including Analysis, Design, Development, Implementation, and Evaluation. The needs analysis in this study was carried out based on analysis of field condition, student analysis, and learning analysis.  The results obtained in this study were thematic learning tools based on the Imeo Kambing’s Game to develop knowledge of earthquake mitigation awareness for elementary school students in Kepahiang Regency which could be implemented in grade IV of Elementary Schools.  The learning theme used is "tema daerah tempat tinggalku", the sub-theme is " Peristiwa Alam di Sekitari tempat tinggalku".  The results of the curriculum analysis show that thematic learning tools based on the Imeo Kambing’s Game for elementary school students' knowledge of earthquake mitigation awareness can be developed.Keyword: earthquake mitigation awareness, traditional game, integrated thematic learning.